Type 3 Dens Invagination. Diagnosis and comprehensive treatment - Degasiuk Виктор Викторович (Actual Dentistry, 2021)
Object: researching the combination of endodontic and surgical treatment of a tooth with developing dens invaginatus pathology. Materials and methods. X-ray diagnostics were performed with the Veraview X800 Morita. Irrigation with sodium hypochlorite solution 5.25 % with additional ultrasound treatmentabd 17 % EDTA solution we e used for drug treatment of invagination and the main channel. The root canal and invagination, due to a non-standard structure, were handled by VDW hand tools combined with the Aurum BLUE (Meta Biomed) machine tool. Constant obturation was performed by the method of vertical compaction «Siller-AN plus». During the surgical stage, Langer (Hu-Friedy) periodontal curettes, CL 8 (Hu-Friedy) curettage spoon, 141-004-31W Oval Spoon Excavator (Hu-Friedy) were used; access to the focus was formed using a piezo surgical spherical nozzle (CE 1, Piezotome Solo (Satelec, Akteon). 4583 Kohler needle holder was used for suturing, suture material—polypropylene 5.0. The bone defect was filled with xenogenic material BIO GEN cancellous size 2/3 mm, 2.0 (Biotek), the barrier membrane—BIOCOLLAGEN (Biotek), the periodontal defect was filled with BIO GEN mix (Biotek).